Online political memes and Youth Political engagement in Singapore - Sreekumar, T. T.; Vadrevu, Shobha (AoIR Selected Papers of Internet Research, 2013)
This paper explores the practice of posting static visual online memes on social media by political actors to convey messages that comment on the ruling party and its policies in Singapore. The paper presents a discussion based on semiotic analysis of popular memes and interviews with Singaporeans aged 18-24 to understand the ways in which circulation of memes influence the quality of political engagement. The results of the analysis suggest that the memes hold the potential for enhancing political engagement among a citizenry that is often seen as depoliticised and apathetic. Memes via their appearance on Facebook and other social media platforms socialise citizens to become critical of the status quo. Memes that attract youth’s attention follow general patterns of satirically commenting on the regime’s carefully articulated narratives of progress and efficiency and constructing subversive counter narratives infused with wit, sarcasm and parody.